Technology Usage Among Construction Students The Moderating Role Of Gender - Ramayah, T.; Jaafar, Mastura (Penerbit Universiti Sains Malaysia, 2008)
This study examines the impact of perceived usefulness and perceived ease of use on the extent of personal computer (PC) usage among a group of undergraduates at the School of Housing, Building and Planning, Universiti Sains Malaysia. It also looks at the moderating role of gender in the above said relationship. Data was collected using a structured questionnaire. A total of 244 students responded to the survey. Results showed that perceived ease of use (β = 0.309, p < 0.01) was positively related to PC usage. A surprising finding of this study was that perceived usefulness was not a significant predictor of PC usage whereas perceived ease of use was. This can be explained in the context of mandated use where the usefulness is no longer an issue and ease of use becomes the primary concern. Gender was not a moderator in the above said relationship but was a significant independent predictor of usage. Males exhibited higher usage of the PC compared to the female students.